Teachers' Attitudes Towards the Teaching of Social Studies in Prestea Huni - Valley Municipality: Taking stance from the Structural Functionalist Theory of Education - Mensah, Ronald Osei; Kwegyiriba, Adwoa; Frimpong , Agyemang (Technium Social Sciences Journal, 2022)
This study sought to examine the attitude of teachers towards the teaching and learning of the Social Studies in Junior High Schools in the Prestea Huni-Valley Municipality. This study sampled 70 participants for the study. Seventy (70) Junior High School social studies teachers were randomly sampled from the Prestea Huni-Valley Municipality. The research was qualitative and descriptive in nature and a self-developed and structured questionnaire was used to collect data for the study. The study was informed by the Structural functionalist theory of education by examining the dominant role of teachers in education. The findings of the study revealed teachers have low status attached to the subject, low morale, and low confidence level in teaching Social Studies among others. The study, therefore, recommends teachers should develop a positive attitude toward the teaching of social studies by exerting confidence in teaching the subject.